Bringing arbitration (taḥkīm) and conciliation (ṣulḥ) under the qāḍī’s purview in Mālikī al-Andalus (10th to 12th centuries C.E.) - Delfina Serrano (Université de Provence, 2016)
This paper examines Mālikī discourses on arbitration and conciliation in a time in which al-Andalus experienced a series of political, intellectual and ideological developments that affected deeply the approach to received wisdom, the judicial policy, and the jurists’ self-perception of their role in society as mediators and peace makers. This is illustrated through the works of two of the most relevant Mālikī fuqahā’ of the period: al-Bājī (403-474/1013-1081) and Ibn Rushd al-Jadd (450-520/1058-1126). They acknowledge arbitration as a valid conflict resolution strategy, though inferior and subservient to qāḍīship, while restricting, mostly on ethical grounds, the right to resort to the widespread practice of conciliation.